Diagenetic history of late Oligocene-early Miocene carbonates in East Sabah, Malaysia - Zainal Abidin, N.S. (Institute of Physics Publishing, 2017)
Limestones are particularly susceptible to drastic early diagenesis modifications, mainly cementation and dissolution. During the early Miocene, a major tectonic deformation has caused a widespread of uplift in Sabah. This has resulted change in depositional environment from deep to shallow marine, which favours the deposition of Gomantong Limestone. This study aims to investigate the diagenetic history of Gomantong Limestone in East Sabah. Thorough understanding of the diagenetic processes may provide data to unravel the tectonic activities which affected the reservoir quality of the carbonates. Combining the data from comprehensive petrographic analysis, and Scanning Electron Microscopy (SEM) of 30 samples, two main cements type were identified. These are microcrystalline cement and Mg-calcite cement of granular and blocky mosaics which are dominantly seen in all samples. The sequence of diagenesis events are determined as (1) micritization; (2) grain scale compaction; (3) cementation (pore-filling); (4) mechanical compaction and cementation infilling fractures and (5) chemical compaction. These diagenetic events are interpreted as reflection of changes in diagenetic environment from shallow marine to deep burial. The massive cementation in the Gomantong Limestone has resulted into a poor reservoir quality. © Published under licence by IOP Publishing Ltd.